Verbascoside enhances radiosensitivity of hepatocellular carcinoma cells through regulating miR‐101‐3p/Wee1 axis. Issue 4 (26th January 2022) - Sun, Lin; Cai, Huangxing; Zhou, Tengchao; Xiang, Hua; Long, Lin
Abstract: Verbascoside is a kind of phenylpropanoid glycoside derived from multiple medicinal plants, exerting anti‐tumor effects in diverse human malignancies. However, the function of Verbascoside on the radiosensitivity of hepatocellular carcinoma (HCC) cells remains unknown. Human Huh7 and HepG2 cell lines were treated with Verbascosideis, and cell viability was detected with cell counting kit‐8 (CCK‐8) assay. Quantitative real‐time polymerase chain reaction (qRT‐PCR) was applied to detect miR‐101‐3p expression, and Western blot was used to quantify the expression of WEE1 G2 checkpoint kinase (WEE1). Then, CCK‐8 and flow cytometry assays were used to detect the proliferation and apoptosis of HCC cells after Verbascoside and X‐ray combined treatment, and the expressions of WEE1 and apoptosis‐related proteins Bax and Bcl‐2 were detected by Western blot. Verbascoside could improve the radiosensitivity of HCC cells in a dose‐dependent manner. Verbascoside increased the expression of miR‐101‐3p but reduced WEE1 expression in HCC cells. Additionally, WEE1 was identified as a target of miR‐101‐3p. MiR‐101‐3p inhibition or WEE1 overexpression could reverse the effect of Verbascoside on the viability and apoptosis of HCC cells. Verbascoside increases the radiosensitivity of hepatocellular carcinoma cells via modulating miR‐101‐3p/WEE1 axis.